HASIL BELAJAR SAINS FISIKA DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INVESTIGASI KELOMPOK PADA SISWA KELAS V SD NEGERI 022 TAMPAN PEKANBARU - Zulirfan Zulirfan (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2007)
The puspose of this research was to find the students physics science learning achievement throughgroup investigation of cooperative learning model to the light and its properties topic. The subject of thisresearch was 47 students of V class SDN 022 Tampan Pekanbaru on 2006/2007 academic’s year. Theinstrument of collecting data was achievement test. Achievement test consist of: cognitive test and scienceprocess skill test. The desciptive analysis showed that the average of students digestibility to the cognitiveand science process skill are catagorized very good.Key words: cognitive, group investigation, science process skill